Philosophy in practice? Doctoral struggles with ontology and subjectivity in qualitative interviewing. Issue 2 (April 2015) - McLachlan, Christopher J; Garcia, Reece J
This article presents an auto-ethnographic, narrative account of the struggles we – as doctoral students working in a business school – experienced navigating the link between research philosophy and methodology. We focus on a popular philosophical perspective among doctoral students: critical realism. In particular, we use an illustrative example of how we sought to apply this seemingly abstract philosophical perspective in practice in our qualitative interviews, using what we term the ontological whats and epistemological hows . Our initial critical realist approach proved inadequate, however, prompting us to understand qualitative interviewing in more social constructionist terms. Given this, we suggest that doctoral students (and researchers) are reflexive and provocative in their use of applying research philosophy to methodology. In sharing our experiences, we offer a pedagogical contribution for fellow doctoral students and qualitative researchers alike.